A formação da atitude na compra de produtos de luxo: um estudo na cidade de São Paulo - Morais, Kleber Souza (2006)
The study of the consumer behavior is an important tool to the elaboration of the company s strategy that aim to conquer the market in which they act, by offering products that the consumers desire and need. Among the factors that constitute the consumer behavior, the attitude has a significant value, because it can explain the reason of some products consumption. This work constitutes a research about the formation of the attitude in the market of the luxury in São Paulo city. This research analyzed the behavior of the luxury consumers, looking for to understand the formation of the attitude of purchase from two referring theoretical models to the consumer behavior: model of multiple attributes of Fishbein and ABC model of attitude. The Fishbein multiple attributes model allows to understand which attribute is most relevant to the consumer in the consumption attitude formation. From this most relevant attribute, the ABC attitude model allows to classify it as an affective, behavioral, or cognitive factor. After the accomplishment of the research and application of these two theoretical models, it was concluded that the cognitive factors have more relevance to the consumers of luxury in São Paulo city. Although the behavioral factors also to present a significative relevance to the luxury consumers, the research evidenced that the cognitive factor have main influence when the consumers are doing their purchases, for example, the product quality, the attendance and the store physical installations